From Babel to Nehemiah: A Theological Reading of Magnifica Humanitas and the Governance of Artificial Intelligence - Raymond Rubianto Tjandrawinata (Indonesian Journal of Multidisciplinary Science, 2026)
This study reads the encyclical within its own theological context and questions what vision of systemic governance is implied in its argument. This reading is organized through the Systems Shift heuristic a seven-element framework drawn from socio-technical transition theory, leverage point analysis, lock-in studies, Responsible AI research, and AI governance literature but this framework serves to support the encyclical's argument, not to organize it. The study's central argument is that Magnifica Humanitas opposes two competing civilizational scripts. Babel names a social order dominated by concentrated technical power, the idolatry of profit, homogenization, and the functional reduction of human beings to data and performance. Nehemiah names the opposite order: patient reconstruction, distributed responsibility, prayerful wisdom, and the protection of the vulnerable. Leo XIV himself framed the AI ??era through these biblical images, and this paper shows that this framing carries the full weight of the encyclical’s theological anthropology: the measure of the technological order is the Incarnation the Word made flesh who reveals the human person as irreducibly embodied, relational, free, and called to communion. Five new theological dimensions are developed and integrated: (1) Trinitarian communion as the theological foundation of the Nehemiah paradigm; (2) structural sin as the proper theological name for the Babel configuration; (3) pneumatology as the basis of shared understanding; (4) incarnational biology as a deepening of Christological anthropology against AI reductionism; and (5) Marian eschatology the grammar of the Magnificat as the encyclical’s concluding horizon for the human city.